2021
DOI: 10.1186/s13059-021-02531-8
|View full text |Cite
|
Sign up to set email alerts
|

A systems genetics approach reveals PbrNSC as a regulator of lignin and cellulose biosynthesis in stone cells of pear fruit

Abstract: Background Stone cells in fruits of pear (Pyrus pyrifolia) negatively influence fruit quality because their lignified cell walls impart a coarse and granular texture to the fruit flesh. Results We generate RNA-seq data from the developing fruits of 206 pear cultivars with a wide range of stone cell contents and use a systems genetics approach to integrate co-expression networks and expression quantitative trait loci (eQTLs) to characterize the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 132 publications
(98 reference statements)
0
28
0
1
Order By: Relevance
“…In the latest study, herbaceous peony increased the layers of thickened secondary cells and lignin accumulation, resulting in enhanced stem strength and demonstrably straight stems [ 33 ]. There was a positive correlation between lignin, cellulose, and stone cell contents in 206 sand pear cultivars [ 34 ]. Therefore, we speculated that low lignin synthesis might lead to low peel hardness and easy cracking.…”
Section: Discussionmentioning
confidence: 99%
“…In the latest study, herbaceous peony increased the layers of thickened secondary cells and lignin accumulation, resulting in enhanced stem strength and demonstrably straight stems [ 33 ]. There was a positive correlation between lignin, cellulose, and stone cell contents in 206 sand pear cultivars [ 34 ]. Therefore, we speculated that low lignin synthesis might lead to low peel hardness and easy cracking.…”
Section: Discussionmentioning
confidence: 99%
“…This is opposed by PbBZR1, which suppresses the activation of the promoters of lignin biosynthesis genes PbCOMT3 and PbHCT6 , and transient silencing PbBZR1 in pear increased lignin content and induced the expression of 15 lignin biosynthetic genes (Cao et al, 2020). Wang et al (2021) have characterized a NAC TF, PbrNSC (NAC STONE CELL PROMOTING FACTOR), which is phylogenetically related to AtNST1/2/3, as a regulator of lignocellulose formation associated with stone cells in pear fruit by integrating co‐expression networks and eQTLs (expression QTL) in 206 pear cultivars. The dual‐luciferase assay showed that PbrNSC could activate the PbrMYB169 , Pbr4CL4 , and PbrLAC4 promoters and genetic complementation experiments showed that PbrNSC could rescue the pendent inflorescence stem of nst1 / nst3 Arabidopsis , which is a symptom of suppressed SCW thickenings (Wang et al, 2021).…”
Section: Transcriptional Regulation Of Fleshy Fruit Lignificationmentioning
confidence: 99%
“…Wang et al (2021) have characterized a NAC TF, PbrNSC (NAC STONE CELL PROMOTING FACTOR), which is phylogenetically related to AtNST1/2/3, as a regulator of lignocellulose formation associated with stone cells in pear fruit by integrating co‐expression networks and eQTLs (expression QTL) in 206 pear cultivars. The dual‐luciferase assay showed that PbrNSC could activate the PbrMYB169 , Pbr4CL4 , and PbrLAC4 promoters and genetic complementation experiments showed that PbrNSC could rescue the pendent inflorescence stem of nst1 / nst3 Arabidopsis , which is a symptom of suppressed SCW thickenings (Wang et al, 2021). MicroRNAs (miRNAs) have also been implicated in lignification processes.…”
Section: Transcriptional Regulation Of Fleshy Fruit Lignificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional limitations of the use of RNA-seq data for variant calling are due to more complicated bioinformatics processing. Specific pipelines must be used to reduce possible false positives resulting from mapping errors induced by splicing events, RNA editing and allele-specific expressions [127,128].…”
Section: Rna Sequencingmentioning
confidence: 99%